2019
DOI: 10.1186/s42358-019-0092-6
|View full text |Cite
|
Sign up to set email alerts
|

Lower genital tract infections in young female juvenile idiopathic arthritis patients

Abstract: Background: To evaluate human papillomavirus (HPV), Chlamydia trachomatis (CT) and Neisseria gonorrhoeae (NG) infections in juvenile idiopathic arthritis (JIA) patients. Methods: After exclusion, 33 female adolescent and young JIA patients (ILAR criteria) and 28 healthy controls were selected for this study. Demographic data, gynecological, sexual function, cervical cytology and histological abnormalities were evaluated. JIA clinical/laboratorial parameters and treatment were also assessed. HPV-DNA, CT-DNA and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…A cross‐section study by Ferreira et al on lower genital tract infections in 33 patients with juvenile arthritis on 15–20 mg of methotrexate per week tested cervical specimens for the presence of HPV, Chlamydia trachomatis and Neisseria gonorrhoeae DNA 22 . The frequency of HPV infection was higher in juvenile arthritis patients than in controls, however, without statistical significance (30% vs. 11%, p = 0.155); therefore, the authors assumed that the drug does not seem to increase the risk of HPV infections.…”
Section: Resultsmentioning
confidence: 99%
“…A cross‐section study by Ferreira et al on lower genital tract infections in 33 patients with juvenile arthritis on 15–20 mg of methotrexate per week tested cervical specimens for the presence of HPV, Chlamydia trachomatis and Neisseria gonorrhoeae DNA 22 . The frequency of HPV infection was higher in juvenile arthritis patients than in controls, however, without statistical significance (30% vs. 11%, p = 0.155); therefore, the authors assumed that the drug does not seem to increase the risk of HPV infections.…”
Section: Resultsmentioning
confidence: 99%
“…The discrimination of seroreactivity to C. trachomatis serotypes and discrimination with C. pneumoniae was by microimmunofluorescence [10]. Subsequently, immunoenzymatic assays [11] were made available for the detection of antibodies. In the 2000s, methods of detecting antigens in situ by immunohistochemistry [12] and nucleic acids were used to confirm infection with C. trachomatis [13,14].…”
Section: Methodsmentioning
confidence: 99%
“…Some authors measure up to 3.5% of high-grade lesions on smear in a group of 85 lupus patients against 0.5% in healthy controls [ 8 ]. One study found a higher frequency of HPV infection among patients with juvenile idiopathic arthritis (JIA) without significance [ 9 ]. The cause of this interaction is not yet known.…”
Section: Introductionmentioning
confidence: 99%